Effect of the human endotoxin challenge on tedizolid tissue penetration. Issue 1 (25th October 2022) - Jorda, Anselm; Wulkersdorfer, Beatrix; Schoergenhofer, Christian; Matzneller, Peter; al Jalali, Valentin; Bauer, Martin; Wölfl‐Duchek, Michael; Lackner, Edith; Dorn, Christoph; Jilma, Bernd; Zeitlinger, Markus
Abstract : The effects of the human endotoxin challenge on tissue pharmacokinetics are unknown. In the present study, we aimed to assess the effect of the endotoxin challenge on interstitial fluid pharmacokinetics of tedizolid in healthy volunteers using intramuscular microdialysis. Eight healthy male subjects were treated with 200 mg of tedizolid phosphate for 6 days. On Day 6, an intravenous bolus of lipopolysaccharide (LPS) (2 ng/kg body weight) was administered. LPS infusion did not affect plasma pharmacokinetics of tedizolid. In contrast, following LPS infusion, median muscle tissue f AUC (0.83 [0.75–1.15] vs . 1.14 [1.11–1.43] mg × h/L, P = .0078) and muscle tissue f Cmax (0.15 [0.14–0.19] vs . 0.19 [0.18–0.24] mg/L, P = .0078) were significantly increased by 38% and 24%, respectively. The human endotoxin challenge was associated with increased tissue concentrations of tedizolid, without affecting its plasma concentration–time profile. The human endotoxin challenge combined with microdialysis may be used to investigate the influence of systemic inflammation on tissue pharmacokinetics.